Developmental Programmed Cell Death Involved in Ontogenesis of Dictamnus dasycarpus Capitate Glandular Hairs - Yafu Zhou; Gen Li; Guijun Han; Lulu Xun; Shaoli Mao; Luyao Yang; Yanwen Wang (Plants, 2023)
Plant glandular trichomes have received much attention due to their commercial and biological value. Recent studies have focused on the development of various glands in plants, suggesting that programmed cell death (PCD) may play an important role during the development of plant secretory structures. However, the development processes and cytological characteristics in different types of plant secretory structures differed significantly. This study aims to provide new data on the developmental PCD of the capitate glandular hairs in Dictamnus dasycarpus. Light, scanning, immunofluorescence labeling, and transmission electron microscopy were used to determine the different developmental processes of the capitate glandular hairs from a cytological perspective. Morphologically, the capitate glandular hair originates from one initial epidermal cell and differentiates into a multicellular trichome characterized by two basal cells, two lines of stalk cells, and a multicellular head. It is also histochemically detected by essential oils. TUNEL-positive reactions identified nuclei with diffused fluorescence or an irregular figure by DAPI, and Evans blue staining showed that the head and stalk cells lost their viability. Ultrastructural evidence revealed the developmental process by two possible modes of PCD. Non-autolytic PCD was characterized by buckling cell walls and degenerated nuclei, mitochondria, plastids, multivesicular body (MVB), and end-expanded endoplasmic reticulum in the condensed cytoplasm, which were mainly observed in the head cells. The MVB was detected in the degraded vacuole, a degraded nucleus with condensed chromatin and diffused membrane, and eventual loss of the vacuole membrane integrity exhibited typical evidence of vacuole-mediated autolytic PCD in the stalk cells. Furthermore, protoplasm degeneration coupled with dark oil droplets and numerous micro-dark osmiophilic substances was observed during late stages. The secretion mode of essential oils is also described in this paper.